Preaching in the Context of Pluralistic Society from the Perspectiveof Reformed Theology - Hyun-Jong Jung (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2026)
Plurality is an undeniable empirical reality, especially in the Indonesian context. This reality poses a challenge for preachers. The questions that must be answered are: how should a preacher convey biblical truth in the context of this pluralistic society? How should preachers proclaim the Gospel? What is the perspective of Reformed theology on this matter? This research uses a literature review method, in which I will explore sources related to the themes discussed above. The books and articles I utilize are largely part of Reformed theology, in order to gain sufficient insight into Reformed theology's perspective on this issue. The conclusions of this research clearly illustrate that in delivering a biblical sermon, a preacher must pay close attention to the method of exploring the Bible correctly and responsibly. In accordance with Reformed theology's belief, "theology from above" must be a priority. The Bible must be the primary source as the sole standard of truth, not heartwarming stories, or the like. Preachers must also adhere firmly to the core doctrines of Reformed theology. The most important thing is that in the sermon, Christ must be the main message conveyed, surpassing other things.